Evaluating the K-13 Versus Merdeka Curriculum : Impacts on Primary, Junior, and Senior High School Education in Indonesia - Endra Priawasana; Singgih Subiyantoro (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to evaluate the impacts of the 2013 Curriculum and the Merdeka Curriculum on primary, junior, and senior high school education in Indonesia. The 2013 Curriculum was introduced to enhance critical thinking, creativity, and character education, while the Merdeka Curriculum emphasizes greater flexibility, independence, and student-centered learning approaches. This study used a mixed-methods with a comparative analysis to assess educational outcomes, teacher and student adaptability, and overall satisfaction within these distinct curricular contexts. Data was collected via surveys, interviews, and academic performance metrics from a representative sample of schools across different regions of Indonesia. Quantitative data from surveys were analyzed using descriptive statistics and inferential statistics, including t-tests and ANOVA, to compare student engagement levels and academic performance under both curricula. Qualitative data from interviews and observations were coded and analyzed thematically to capture the nuanced experiences and perceptions of teachers and students. Research findings show that the 2013 Curriculum and the Merdeka Curriculum have their strengths and weaknesses, the latter is generally viewed more favorably by teachers and students for its emphasis on flexibility, learner autonomy, and holistic development. The Merdeka Curriculum has shown promise in fostering student engagement, critical thinking skills, and creativity, yet challenges persist in terms of implementation, teacher training, and resource allocation. A novel finding of this research is the significant improvement in holistic assessment practices under the Merdeka Curriculum, which better captures student competencies beyond standardized testing. Additionally, the study highlights the critical role of equitable resource allocation and continuous professional development for teachers in the successful implementation of curriculum reforms.